2007
DOI: 10.1186/1471-2202-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Superior sensation: superior colliculus participation in rat vibrissa system

Abstract: Background: The superior colliculus, usually considered a visuomotor structure, is anatomically positioned to perform sensorimotor transformations in other modalities. While there is evidence for its potential participation in sensorimotor loops of the rodent vibrissa system, little is known about its functional role in vibrissa sensation or movement. In anesthetized rats, we characterized extracellularly recorded responses of collicular neurons to different types of vibrissa stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
4
23
0
Order By: Relevance
“…Previously, Hemelt and Keller (2007) have reported that the neurons of the superior colliculus have more angular selectivity when compared to neurons in of barrel: 16% of barrel cortex neurons have a high selectivity index in comparison to 43% of collicular neurons. Thus, it is truly significant to see such a clear spatial representation of the angular selectivity in the barrel area.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, Hemelt and Keller (2007) have reported that the neurons of the superior colliculus have more angular selectivity when compared to neurons in of barrel: 16% of barrel cortex neurons have a high selectivity index in comparison to 43% of collicular neurons. Thus, it is truly significant to see such a clear spatial representation of the angular selectivity in the barrel area.…”
Section: Discussionmentioning
confidence: 98%
“…Thus it is a logical inference that the whisker's angular selectivity is a key element of barrel cortex stimulus representations. Angular selectivity of the neurons has been described at different levels of the vibrissae system (Li and Ebner, 2007;Minnery and Simons, 2003;Hemelt and Keller, 2007) but its mechanism is still not clarified completely.…”
Section: Discussionmentioning
confidence: 99%
“…The results also revealed a large increase in SC firing during active exploration. This is significant because during anesthesia, many whisker-responsive cells have nil spontaneous firing (Cohen et al 2008;Hemelt and Keller 2007). A large number of variables may contribute to the increased firing.…”
Section: Sc Spontaneous Firingmentioning
confidence: 98%
“…The superior colliculus is well known to be involved in orienting responses to stimuli from a wide range of modalities, including somatosensory, auditory, and visual (Dean et al 1989;Meredith and Stein 1985;Schneider 1969;Sparks 1986;Sprague and Meikle 1965;Stein 1998;Stein and Meredith 1993;Wurtz and Albano 1980). Neurons in the intermediate layers of the superior colliculus of rats are highly responsive to vibrissa (whisker) stimulation Castro-Alamancos 2007, 2010;Cohen et al 2008;Grunwerg and Krauthamer 1990;Hemelt and Keller 2007;McHaffie et al 1989;Weldon and Best 1992). These whisker responses are driven by direct inputs from the trigeminal complex (trigeminotectal; peak1 at ϳ5 ms poststimulus) followed by activity returning from the barrel cortex (corticotectal; peak2 at ϳ12 ms) (Cohen et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Cells in the intermediate layers of the superior colliculus are highly responsive to passive touch of vibrissa (i.e., deflection of stationary whiskers) Castro-Alamancos 2007, 2010b;Cohen et al 2008;Grunwerg and Krauthamer 1990;Hemelt and Keller 2007;McHaffie et al 1989). Superior colliculus passive touch responses are driven by direct inputs from the trigeminal complex (trigeminotectal; peak1) followed by activity returning from the barrel cortex (corticotectal; peak2) in both anesthetized (Cohen et al 2008) and freely behaving rats (Cohen and Castro-Alamancos 2010a).…”
mentioning
confidence: 99%